2020
DOI: 10.1007/s00521-020-05139-4
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for total cloud cover prediction

Abstract: Accurate and reliable forecasting of total cloud cover (TCC) is vital for many areas such as astronomy, energy demand and production, or agriculture. Most meteorological centres issue ensemble forecasts of TCC; however, these forecasts are often uncalibrated and exhibit worse forecast skill than ensemble forecasts of other weather variables. Hence, some form of post-processing is strongly required to improve predictive performance. As TCC observations are usually reported on a discrete scale taking just nine d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 51 publications
(62 reference statements)
2
23
0
Order By: Relevance
“…The overall level of improvements achieved via statistical postprocessing of the solar irradiance forecasts of the raw ensemble are comparable to meteorological variables such as precipitation accumulation (Scheuerer, 2014;Baran and Nemoda, 2016) or total cloud cover (Baran et al, 2021) in case of the ICON-EPS dataset, and slightly larger for the AROME-EPS data. Post-processing ensemble predictions of those variables is often seen as a more difficult task compared to variables such as temperature (Gneiting et al, 2005) or wind speed (Thorarinsdottir and where substantially larger improvements can be achieved.…”
Section: Discussionmentioning
confidence: 78%
“…The overall level of improvements achieved via statistical postprocessing of the solar irradiance forecasts of the raw ensemble are comparable to meteorological variables such as precipitation accumulation (Scheuerer, 2014;Baran and Nemoda, 2016) or total cloud cover (Baran et al, 2021) in case of the ICON-EPS dataset, and slightly larger for the AROME-EPS data. Post-processing ensemble predictions of those variables is often seen as a more difficult task compared to variables such as temperature (Gneiting et al, 2005) or wind speed (Thorarinsdottir and where substantially larger improvements can be achieved.…”
Section: Discussionmentioning
confidence: 78%
“…ANNs, including Multilayer Perceptron, deep ANNs, and other machine learning models, are constantly being improved and widely used for the forecasting of air temperature [64], rainfall [36,37,65], cloudiness [66], and wind speed [67], which proves that these are forward-looking models that are worthy of constant research and improvement for forecasting purposes. To summarize, the most frequently forecasted condition in the above works was temperature; several studies have similarly found the use of models for wind speed prediction, and the most frequently used machine learning model for this purpose was a multilayer Artificial Neural Network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hamill & Whitaker [29] show initial explorations of those techniques on re-forecast datasets, also used in this article, for temperature at 850 hPa (T850) and geopotential at 500 hPa (Z500). Advances in neural networks have only recently reached the field of ensemble models in weather forecasting, focusing on its application to specific weather stations [9,30] or global interpolations [31]. We expand on this work by applying DNNs on the novel task of improving the forecast skill for global predictions, specifically extreme weather forecasts, while reducing their computational costs.…”
Section: Introductionmentioning
confidence: 99%